Effect of respiratory motion on free‐breathing 3D stack‐of‐radial liver R2∗ relaxometry and improved quantification accuracy using self‐gating - Zhong, Xiaodong; Armstrong, Tess; Nickel, Marcel D.; Kannengiesser, Stephan A.R.; Pan, Li; Dale, Brian M.; Deshpande, Vibhas; Kiefer, Berthold; Wu, Holden H. (Magnetic resonance in medicine, 2020)
Purpose To develop an accurate free‐breathing 3D liver R2∗ mapping approach and to evaluate it in vivo. Methods A free‐breathing multi‐echo stack‐of‐radial sequence was applied in 5 normal subjects and 6 patients at 3 Tesla. Respiratory motion compensation was implemented using the inherent self‐gating signal. A breath‐hold Cartesian acquisition was the reference standard. Proton density fat fraction and R2∗ were measured and compared between radial and Cartesian methods using Bland‐Altman plots. The normal subject results were fitted to a linear mixed model (P < .05 considered significant). Results Free‐breathing stack‐of‐radial without self‐gating exhibited signal attenuation in echo images and artifactually elevated apparent R2∗ values. In the Bland‐Altman plots of normal subjects, compared to breath‐hold Cartesian, free‐breathing stack‐of‐radial acquisitions of 22, 30, 36, and 44 slices, had mean R2∗ differences of 27.4, 19.4, 10.9, and 14.7 s−1 with 800 radial views, and they had 18.4, 11.9, 9.7, and 27.7 s−1 with 404 views, which were reduced to 0.4, 0.9, −0.2, and −0.7 s−1 and to −1.7, −1.9, −2.1, and 0.5 s−1 with self‐gating, respectively. No substantial proton density fat fraction differences were found. The linear mixed model showed free‐breathing radial R2∗ results without self‐gating were significantly biased by 17.2 s−1 averagely (P = .002), which was eliminated with self‐gating (P = .930). Proton density fat fraction results were not different (P > .234). For patients, Bland‐Altman plots exhibited mean R2∗ differences of 14.4 and 0.1 s−1 for free‐breathing stack‐of‐radial without self‐gating and with self‐gating, respectively, but no substantial proton density fat fraction differences. Conclusion The proposed self‐gating method corrects the respiratory motion bias and enables accurate free‐breathing stack‐of‐radial quantification of liver R2∗.